2010
DOI: 10.2174/092986710791698549
|View full text |Cite
|
Sign up to set email alerts
|

A Role of GABA Analogues in the Treatment of Neurological Diseases

Abstract: gamma-Amino butyric acid is an extremely important inhibitory neurotransmitter in the mammalian central nervous system and is essential for the overall balance between neuronal excitation and inhibition. It is well documented that GABA deficiency is associated with several important neurological disorders such as Huntington's chorea, Parkinson's and Alzheimer's disease and other psychiatric disorders, like anxiety, depression, pain, panic, or mania. Although, it is known that increasing the brain concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 69 publications
0
70
0
5
Order By: Relevance
“…Mounting evidence implicates the GABAergic system, and specifically the tonic form of inhibition, as a potential therapeutic target for developing novel treatments for other brain disorders such as epilepsy, premenstrual dysphoric disorder and stroke [22,29,30,31]. In relation to FXS, it has been reported that GABA exposure during development can rescue the biochemical, morphological, and behavioral phenotypes of the Drosophila model of FXS [20], and taurine, a GABA A receptor agonist, improves cognitive functions in a mouse model of FXS [21].…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence implicates the GABAergic system, and specifically the tonic form of inhibition, as a potential therapeutic target for developing novel treatments for other brain disorders such as epilepsy, premenstrual dysphoric disorder and stroke [22,29,30,31]. In relation to FXS, it has been reported that GABA exposure during development can rescue the biochemical, morphological, and behavioral phenotypes of the Drosophila model of FXS [20], and taurine, a GABA A receptor agonist, improves cognitive functions in a mouse model of FXS [21].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, GABA has been shown as an antioxidant, blood sugar reducing and vasorelaxant agent (20,24,36-38). The renal tissues are documented to be involved in GABA synthesis and the kidneys are known to possess various subtypes of GABA receptors (39,40). It seems that GABA could be involved in regulating renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Normal brain function requires a balance between excitatory and inhibitory inputs that converge onto neurons in the central nervous system, with imbalance producing major neurological disorders (e.g., Gajcy et al, 2010; Naylor, 2010). Unilateral vestibular deafferentation destroys the balance in vestibular nuclei neurons by removing a major excitatory input.…”
Section: Spontaneous Synaptic Activity After Unilateral Peripheral Vementioning
confidence: 99%